Saliva pad for transesophageal ultrasound and cardiac examination

By designing a saliva pad containing a water absorption layer and a waterproof layer, the problems of inconvenience of saliva treatment and cross-infection during transesophageal ultrasound and cardiac examinations are solved, and the effect of efficient absorption and dispersion of oral fluids is achieved, and the risk of bacterial growth is reduced.

CN119636197AInactive Publication Date: 2025-03-18SHUNDE HOSPITAL OF GUANGZHOU UNIV OF TRADITIONAL CHINESE MEDICINE (SHUNDE DISTRICT HOSPITAL OF TRADITIONAL CHINESE MEDICINE FOSHAN CITY)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411813326.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During transesophageal ultrasound and cardiac examination, the patient's oral secretes excessive saliva. Traditional collection and treatment methods cannot effectively prevent saliva from flowing out, resulting in inconvenience and cross-infection risk.

Method used

A saliva pad consisting of a water absorbing layer and a waterproof layer is designed, made of polyvinyl alcohol, sodium carboxymethylcellulose, modified calcium carbonate and copper/zinc oxide modified chitosan, which has excellent hygroscopicity and antibacterial properties, while the waterproof layer prevents liquid penetration.

Benefits of technology

Effectively absorb and disperse the secreted liquid in the oral cavity, keep the use area dry and comfortable, prevent bacteria from growing, reduce the risk of cross-infection, and use environmentally friendly materials, which are easy to biodegradate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005181475980000131
    Figure BDA0005181475980000131
  • Figure BDA0005181475980000141
    Figure BDA0005181475980000141
Patent Text Reader

Abstract

The invention relates to the technical field of saliva pads, in particular to a saliva pad for transesophageal ultrasound and cardiac examines.The saliva pad comprises a water absorption layer and a waterproof layer, and a preparation method of the water absorption layer comprises the steps that polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate and copper / zinc oxide modified chitosan are added into water to be mixed, spinning the spinning solution to obtain antibacterial fibers, and blending the antibacterial fibers and cotton fibers to obtain the antibacterial cotton fiber. According to the saliva pad for transesophageal ultrasound and cardiac examination, the water absorption and antibacterial property are optimized, and the defects of a traditional method in the aspect of saliva receiving and treating are effectively overcome. According to the saliva pad, the comfort level of a patient can be improved, the workload of medical staff can be reduced, the risk of cross infection can be reduced, and a safer, more comfortable and more efficient solution is provided for the field of medical examination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of saliva pads, and in particular to a saliva pad for transesophageal ultrasound and cardiac examination. Background Art

[0002] In the field of medical examination, transesophageal echocardiography (TEE) and other transesophageal examinations (such as gastroscopy) are common methods for diagnosing heart disease and digestive tract diseases. These examinations usually require the patient to be in a specific position and insert the probe into the esophagus through the mouth to obtain clear images. Although this examination method can provide more accurate diagnostic results, it often causes discomfort to the patient, especially when the mouth and esophagus are irritated, the mouth will secrete too much saliva. Since the patient's mouth cannot be closed, saliva can easily flow out, which brings inconvenience to the examination process and may affect the patient's experience.

[0003] In traditional practice, medical staff often use utensils, paper towels or plastic bags to collect and handle these secretions. However, these methods have many shortcomings. First, they often cannot effectively prevent saliva from flowing out, causing the patient's clothes or examination area to get wet, increasing the patient's discomfort. Secondly, these items need to be replaced frequently, which increases the workload of medical staff and may also interrupt the examination process and reduce the efficiency of the examination. Most importantly, these traditional methods lack antibacterial treatment and cannot effectively prevent bacterial growth, increasing the risk of cross infection. Based on this, the present invention proposes a saliva pad for transesophageal ultrasound and cardiac examination. Summary of the invention

[0004] The purpose of the present invention is to provide a saliva pad for transesophageal ultrasound and cardiac examination, which effectively solves the shortcomings of traditional methods in receiving and processing saliva by optimizing water absorption and antibacterial properties.

[0005] In a first aspect, the present invention provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer. The preparation method of the water-absorbing layer comprises: adding polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, and copper / zinc oxide-modified chitosan into water and mixing them to obtain a spinning solution, spinning the solution to obtain an antibacterial fiber, and blending the antibacterial fiber with cotton fiber to obtain the saliva pad.

[0006] Furthermore, the weight ratio of the polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is (16-18): (22-24): (0.5-1): (1.5-2.5): (260-280).

[0007] Furthermore, the preparation method of the modified calcium carbonate includes: drying the calcium carbonate at a temperature of 50-60°C for 60-80 minutes, mixing a titanate coupling agent with ethanol, adding calcium carbonate, reacting at a temperature of 60-80°C for 80-100 minutes, filtering, washing with acetone, and drying at 70-80°C to obtain modified calcium carbonate.

[0008] Furthermore, the weight ratio of the titanate coupling agent, ethanol and calcium carbonate is 0.05-0.1:6-8:1-2.

[0009] Furthermore, the titanate coupling agent is titanate coupling agent 311.

[0010] Furthermore, the preparation method of the copper / zinc oxide modified chitosan comprises: adding chitosan, copper oxide and zinc oxide into a glacial acetic acid aqueous solution and stirring and mixing at a temperature of 50-60° C., adding glutaraldehyde at a constant temperature and continuing to stir for 15-25 minutes, then adding a sodium hydroxide aqueous solution and continuing to stir for 25-35 minutes, filtering, washing and drying to obtain the chitosan.

[0011] Furthermore, the usage ratio of the chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is (1-2) g: (0.1-0.2) g: (0.2-0.3) g: (240-260) mL: (3-5) mL: (50-60) mL.

[0012] Furthermore, the mass concentration of the glacial acetic acid aqueous solution is 2-3%, and the molar concentration of the sodium hydroxide aqueous solution is 2-3 mol / L.

[0013] Furthermore, the spinning step includes: adding the spinning solution into a 10mL syringe, setting the voltage to 14-16kV, the receiving distance to 11-13cm, and injecting it onto the substrate through a jet device at a feed rate of 0.2-0.3mL / h at room temperature for electrospinning.

[0014] Furthermore, the blending needs to be heat treated at a temperature of 90-100° C. and a heat treatment time of 5-7 minutes.

[0015] The beneficial effects of the present invention are:

[0016] The saliva pad of the present invention uses copper / zinc oxide modified chitosan as a raw material. This material has excellent antibacterial properties, can effectively inhibit the growth and reproduction of bacteria, and reduce the risk of infection. The introduction of antibacterial fibers enables the entire saliva pad to maintain a high degree of cleanliness during use and prolongs its service life. The water-absorbing layer is made of polymer materials such as polyvinyl alcohol and sodium carboxymethyl cellulose. These materials have good hygroscopicity and air permeability, can quickly absorb and disperse the liquid secreted by the oral cavity, and keep the use area dry and comfortable; the provision of the waterproof layer effectively prevents the liquid from penetrating into the lower layer, and maintains the overall dryness of the pad. In addition, the raw materials used in the preparation process of the saliva pad are all environmentally friendly materials, are easy to biodegrade, and will not cause pollution to the environment.

[0017] In the present invention, polyvinyl alcohol and sodium carboxymethyl cellulose are used as base materials for spinning. Polyvinyl alcohol has good water solubility and film-forming property, can form a continuous fiber network, and is beneficial to the absorption and diffusion of liquid; sodium carboxymethyl cellulose has strong hygroscopicity and water retention, and can increase the water absorption and water holding capacity of the fiber.

[0018] The present invention also adds modified calcium carbonate as an auxiliary material, so that it can be filled in the gaps of the fiber and increase the porosity of the fiber, and the increase in porosity helps to increase the specific surface area of ​​the fiber, thereby enhancing the fiber's ability to adsorb moisture; calcium carbonate can be treated with a titanate coupling agent to improve the compatibility between calcium carbonate and polymer materials; and the addition of modified calcium carbonate can change the microenvironment of the fiber, such as improving the air permeability of the fiber and increasing the roughness of the fiber surface; these changes help to reduce the attachment and growth of bacteria on the fiber surface, thereby indirectly improving the antibacterial property of the fiber. In addition, the modified calcium carbonate is also compounded with copper / zinc oxide modified chitosan to further enhance the antibacterial property of the fiber.

[0019] The modified calcium carbonate prepared by using titanate coupling agent 311 as a raw material in the present invention has better dispersibility and reactivity than the modified calcium carbonate modified by titanate coupling agent TC-114 and silane coupling agent KH570, and can form more uniform and stronger chemical bonds on the surface of calcium carbonate. Although titanate coupling agent 311 itself does not directly have antibacterial activity, it may form a microenvironment that is conducive to the release or action of antibacterial substances through combination with calcium carbonate, and the introduction of titanate coupling agent 311 changes the surface properties of calcium carbonate, making it more hydrophilic.

[0020] The present invention also utilizes copper / zinc oxide modified chitosan as an auxiliary material for spinning, wherein chitosan itself has certain water absorption and water retention, which provides a basis for its application in saliva pads. The addition of copper oxide and zinc oxide forms micropores or increases the surface area of ​​chitosan, thereby improving its water absorption speed and water absorption capacity; glutaraldehyde, as a cross-linking agent, may form a chemical bond to more closely combine chitosan and copper / zinc oxide, while maintaining or enhancing the water absorption of chitosan. Copper and zinc are both metal elements with antibacterial activity. Copper ions and zinc ions can destroy the cell membrane of bacteria, inhibit their growth and reproduction, and adding copper oxide and zinc oxide to chitosan can make the chitosan material have a lasting antibacterial property. Chitosan itself also has certain antibacterial properties, mainly due to the fact that its positive charge can interact with the negative charge of the bacterial cell membrane, thereby destroying the integrity of the bacteria. The combination of chitosan and copper / zinc oxide may produce a synergistic effect, further enhancing its antibacterial effect. Compared with copper oxide or zinc oxide alone, the modified chitosan produced a stronger synergistic antibacterial effect. This effect may be due to the combined action of copper ions and zinc ions on the bacterial cell membrane and their interference with the internal metabolic activities of bacteria. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be noted that the average particle size of calcium carbonate in the present invention is 110 nm; the average particle size of copper oxide is 30 nm; the average particle size of zinc oxide is 50 nm; polyvinyl alcohol, BP-05, is from Changchun Chemical Industry, Taiwan Province.

[0023] Example 1

[0024] This embodiment provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0025] Preparation of modified calcium carbonate: drying calcium carbonate at 55°C for 70 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 70°C for 90 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.075:7:1.5;

[0026] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide were added to a 2.5% glacial acetic acid aqueous solution, stirred and mixed at a temperature of 55°C, glutaraldehyde was added at a constant temperature and continued to stir for 20 minutes, and then a 2.5 mol / L sodium hydroxide aqueous solution was added and continued to stir for 30 minutes, and the mixture was filtered, washed and dried.

[0027] The amount ratio of chitosan, copper oxide, zinc oxide, glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1.5g: 0.15g: 0.25g: 250mL: 4mL: 55mL;

[0028] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed, and the obtained spinning solution is added to a 10 mL syringe, the voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, the solution is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber is blended with cotton fiber and heat-treated to obtain the obtained fiber;

[0029] The heat treatment temperature is 95° C., the heat treatment time is 6 min, and the weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 17:23:0.75:2:270.

[0030] Example 2

[0031] This embodiment provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0032] Preparation of modified calcium carbonate: drying calcium carbonate at 50°C for 80 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 60°C for 100 minutes, filtering, washing with acetone, and drying at 70°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.1:6:2;

[0033] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2% and stirred at a temperature of 60°C, glutaraldehyde is added at a constant temperature and stirred for 15 minutes, and then a sodium hydroxide aqueous solution with a concentration of 3 mol / L is added and stirred for 25 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 2g:0.1g:0.3g:240mL:5mL:50mL;

[0034] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed, and the obtained spinning solution is added to a 10mL syringe, the voltage is set to 16kV, the receiving distance is 11cm, and the feed rate is 0.3mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 90°C for 7min; wherein, the weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 16:22:1:1.5:280.

[0035] Example 3

[0036] This embodiment provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0037] Preparation of modified calcium carbonate: drying calcium carbonate at 60°C for 60 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 80°C for 80 minutes, filtering, washing with acetone, and drying at 80°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.05:8:1;

[0038] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide are added to a 3% glacial acetic acid aqueous solution at a temperature of 50°C and stirred and mixed, glutaraldehyde is added at a constant temperature and stirred for 25 minutes, and then a 2 mol / L sodium hydroxide aqueous solution is added and stirred for 35 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1g:0.2g:0.2g:260mL:3mL:60mL;

[0039] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed to obtain a spinning solution, which is added to a 10 mL syringe, the voltage is set to 14 kV, the receiving distance is 13 cm, and the feed rate is 0.2 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at a temperature of 100°C for 5 min. The weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 18:22:1:1.5:280.

[0040] Example 4

[0041] This embodiment provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0042] Preparation of modified calcium carbonate: drying calcium carbonate at 54°C for 68 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 65°C for 95 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.05:6:1;

[0043] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2% and stirred at a temperature of 50°C, glutaraldehyde is added at a constant temperature and stirred for 15 minutes, and then a sodium hydroxide aqueous solution with a concentration of 2 mol / L is added and stirred for 25 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1g: 0.1g: 0.2g: 240mL: 3mL: 5mL;

[0044] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed to obtain a spinning solution, which is added to a 10 mL syringe, the voltage is set to 16 kV, the receiving distance is 13 cm, and the feed rate is 0.3 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at a temperature of 100 ° C and a heat treatment time of 7 min. Among them, the weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 18:24:1:2.5:280.

[0045] Comparative Example 1

[0046] This comparative example provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0047] Preparation of modified calcium carbonate: drying calcium carbonate at 55°C for 70 minutes, mixing titanate coupling agent TC-114 with ethanol, adding calcium carbonate, reacting at 70°C for 90 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent TC-114, ethanol and calcium carbonate is 0.075:7:1.5;

[0048] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2.5% and stirred at a temperature of 55°C, glutaraldehyde is added at a constant temperature and stirred for 20 minutes, and then a sodium hydroxide aqueous solution with a concentration of 2.5 mol / L is added and stirred for 30 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1.5g:0.15g:0.25g:250mL:4mL:55mL;

[0049] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed to obtain a spinning solution, which is added to a 10 mL syringe, the voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 95°C for 6 min. The weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 17:23:0.75:2:270.

[0050] Comparative Example 2

[0051] This comparative example provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0052] Preparation of modified calcium carbonate: drying calcium carbonate at 55°C for 70 minutes, mixing silane coupling agent KH570 with ethanol, adding calcium carbonate, reacting at 70°C for 90 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of silane coupling agent KH570, ethanol and calcium carbonate is 0.075:7:1.5;

[0053] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2.5% and stirred at a temperature of 55°C, glutaraldehyde is added at a constant temperature and stirred for 20 minutes, and then a sodium hydroxide aqueous solution with a concentration of 2.5 mol / L is added and stirred for 30 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1.5g:0.15g:0.25g:250mL:4mL:55mL;

[0054] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed to obtain a spinning solution, which is added to a 10 mL syringe, the voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 95°C for 6 min. The weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 17:23:0.75:2:270.

[0055] Comparative Example 3

[0056] This comparative example provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0057] Preparation of copper / zinc oxide modified chitosan: chitosan, copper oxide and zinc oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2.5% and stirred at a temperature of 55°C, glutaraldehyde is added at a constant temperature and stirred for 20 minutes, and then a sodium hydroxide aqueous solution with a concentration of 2.5 mol / L is added and stirred for 30 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1.5g:0.15g:0.25g:250mL:4mL:55mL;

[0058] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, calcium carbonate, copper / zinc oxide modified chitosan are added to water and mixed, and the obtained spinning solution is added to a 10 mL syringe, the voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 95°C for 6 min. Among them, the weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 17:23:0.75:2:270.

[0059] Comparative Example 4

[0060] This comparative example provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0061] Preparation of modified calcium carbonate: drying calcium carbonate at 55°C for 70 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 70°C for 90 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.075:7:1.5;

[0062] Preparation of zinc oxide modified chitosan: chitosan and zinc oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2.5% and stirred at a temperature of 55°C, glutaraldehyde is added at a constant temperature and stirred for 20 minutes, and then a sodium hydroxide aqueous solution with a concentration of 2.5 mol / L is added and stirred for 30 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1.5g:0.4g:250mL:4mL:55mL;

[0063] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, and zinc oxide-modified chitosan are added to water and mixed to obtain a spinning solution, which is added to a 10 mL syringe. The voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 95°C for 6 min. The weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide-modified chitosan and water is 17:23:0.75:2:270.

[0064] Comparative Example 5

[0065] This comparative example provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0066] Preparation of modified calcium carbonate: drying calcium carbonate at 55°C for 70 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 70°C for 90 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.075:7:1.5;

[0067] Preparation of copper oxide modified chitosan: chitosan and copper oxide are added to a glacial acetic acid aqueous solution with a mass concentration of 2.5% and stirred at a temperature of 55°C, glutaraldehyde is added at a constant temperature and stirred for 20 minutes, and then a sodium hydroxide aqueous solution with a concentration of 2.5 mol / L is added and stirred for 30 minutes, filtered, washed and dried to obtain the chitosan; wherein the amount ratio of chitosan, copper oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is 1.5g:0.4g:250mL:4mL:55mL;

[0068] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, and copper oxide-modified chitosan are added to water and mixed to obtain a spinning solution, which is added to a 10 mL syringe. The voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 95°C for 6 min. The weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide-modified chitosan and water is 17:23:0.75:2:270.

[0069] Comparative Example 6

[0070] This comparative example provides a saliva pad for transesophageal ultrasound and cardiac examination, comprising a water-absorbing layer and a waterproof layer, which are bonded together;

[0071] Preparation of modified calcium carbonate: drying calcium carbonate at 55°C for 70 minutes, mixing titanate coupling agent 311 with ethanol, adding calcium carbonate, reacting at 70°C for 90 minutes, filtering, washing with acetone, and drying at 75°C to obtain modified calcium carbonate; wherein the weight ratio of titanate coupling agent 311, ethanol and calcium carbonate is 0.075:7:1.5;

[0072] Preparation of water-absorbing layer: polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate and chitosan are added into water and mixed to obtain spinning solution, which is added into a 10 mL syringe, the voltage is set to 15 kV, the receiving distance is 12 cm, and the feed rate is 0.25 mL / h. At room temperature, it is injected into the substrate through a jet device for electrostatic spinning to obtain antibacterial fiber, and the antibacterial fiber and cotton fiber are blended and heat-treated at 95 ° C for 6 min. The weight ratio of polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is 17:23:0.75:2:270.

[0073] The water-absorbing layers prepared in Examples 1-4 and Comparative Examples 1-6 were tested by taking samples of 100 mm × 100 mm, the specifications of which were all 200 g / m 2 , the deviation is ±6.

[0074] 1. Water absorption performance: Tested in accordance with Q-320581GOH002-2019 non-woven absorbent pad standard;

[0075] 2. Antibacterial performance: Refer to the method in GB / T20944.3-2008 to test the inhibition rate of the water-absorbing layer against Staphylococcus aureus, Escherichia coli and Candida albicans.

[0076] The test results are shown in Table 1.

[0077] Table 1 Test results

[0078]

[0079]

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A saliva pad for transesophageal ultrasound and cardiac examination, characterized in that: The invention comprises a water-absorbing layer and a waterproof layer. The preparation method of the water-absorbing layer comprises: adding polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate and copper / zinc oxide modified chitosan into water for mixing, obtaining a spinning solution, spinning the solution to obtain antibacterial fiber, and blending the antibacterial fiber with cotton fiber to obtain the waterproof layer.

2. A saliva pad for transesophageal ultrasound and cardiac examination according to claim 1, characterized in that: The weight ratio of the polyvinyl alcohol, sodium carboxymethyl cellulose, modified calcium carbonate, copper / zinc oxide modified chitosan and water is (16-18): (22-24): (0.5-1): (1.5-2.5): (260-280).

3. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 1, characterized in that: The preparation method of the modified calcium carbonate comprises: drying the calcium carbonate at a temperature of 50-60° C. for 60-80 minutes, mixing a titanate coupling agent with ethanol, adding the calcium carbonate, reacting at a temperature of 60-80° C. for 80-100 minutes, filtering, washing with acetone, and drying at a temperature of 70-80° C. to obtain the modified calcium carbonate.

4. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 3, characterized in that: The weight ratio of the titanate coupling agent, ethanol and calcium carbonate is 0.05-0.1:6-8:1-2.

5. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 3, characterized in that: The titanate coupling agent is titanate coupling agent 311.

6. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 1, characterized in that: The preparation method of the copper / zinc oxide modified chitosan comprises: adding chitosan, copper oxide and zinc oxide into glacial acetic acid aqueous solution and stirring and mixing at a temperature of 50-60° C., adding glutaraldehyde at a constant temperature and continuing stirring for 15-25 minutes, then adding sodium hydroxide aqueous solution and continuing stirring for 25-35 minutes, filtering, washing and drying to obtain the chitosan.

7. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 6, characterized in that: The dosage ratio of the chitosan, copper oxide, zinc oxide and glacial acetic acid aqueous solution, glutaraldehyde and sodium hydroxide aqueous solution is (1-2) g: (0.1-0.2) g: (0.2-0.3) g: (240-260) mL: (3-5) mL: (50-60) mL.

8. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 7, characterized in that: The mass concentration of the glacial acetic acid aqueous solution is 2-3%, and the molar concentration of the sodium hydroxide aqueous solution is 2-3 mol / L.

9. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 1, characterized in that: The spinning step comprises: adding spinning solution into a 10 mL syringe, setting the voltage to 14-16 kV, the receiving distance to 11-13 cm, injecting the solution onto a substrate through a jet device at a feed rate of 0.2-0.3 mL / h at room temperature for electrostatic spinning.

10. The saliva pad for transesophageal ultrasound and cardiac examination according to claim 1, characterized in that: After the blending, heat treatment is required, and the temperature of the heat treatment is 90-100° C. and the heat treatment time is 5-7 minutes.